A land of the 'fair go'? Intergenerational earnings elasticity in Australia. Issue 3 (October 2016) - Huang, Yangtao; Perales, Francisco; Western, Mark
Abstract: This paper contributes to the existing literature on income mobility by developing and applying a two‐stage panel regression model and assessing the effects of using different levels of occupational (dis)aggregation and different earnings measures on the magnitude of father–son earnings elasticities in Australia. We find that the overall intergenerational earnings elasticity in Australia between 2001 and 2013 ranges from 0.11 to 0.30. Our preferred estimates lie between 0.24 and 0.28. Elasticity estimates vary depending on the level of occupational (dis)aggregation and earnings measure used: they are highest when two‐digit level occupations and hourly earnings are used, and lowest when four‐digit level occupations and annual earnings are used. We read these findings as indicating that elasticity estimates are sensitive to the use of different data and methods, and researchers should be careful when undertaking cross‐study, cross‐temporal or cross‐national comparisons.